2013
DOI: 10.1590/s1677-5538.ibju.2013.04.18
|View full text |Cite
|
Sign up to set email alerts
|

Extending boundaries in minimally invasive procedures with simultaneous bilateral video endoscopic inguinal lymphadenectomy (veil) for penile cancer: initial Denver health medical center and ABC school of medicine experience and surgical considerations

Abstract: Purpose: To report the surgical technique, procedural outcomes, and feasibility of simultaneous bilateral Video Endoscopic Inguinal Lymphadenectomy (VEIL) in the management of patients with indication for inguinal lymphadenectomy. Surgical Technique: VEIL was applied in all patients using the oncological landmarks (the adductor longus muscle medially, the sartorius muscle laterally and the inguinal ligament superiorly). A 1.5 cm incision was made 2 cm distally to the lower vertex of the femoral triangle. A sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 8 publications
3
17
0
2
Order By: Relevance
“…No matter what kind of incision is used in open inguinal lymphadenectomy, there is a higher chance of complications such as ap necrosis and incision infection [8,9] . Since 2003, some studies have reported the use of VEIL, and this technique is considered safe and effective [10][11][12] . We carried out video endoscopic inguinal lymphadenectomy since 2013, and analyzed the results of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…No matter what kind of incision is used in open inguinal lymphadenectomy, there is a higher chance of complications such as ap necrosis and incision infection [8,9] . Since 2003, some studies have reported the use of VEIL, and this technique is considered safe and effective [10][11][12] . We carried out video endoscopic inguinal lymphadenectomy since 2013, and analyzed the results of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…23 Outra forma de diminuir a morbilidade é a realização da LIMVA bilateral em simultâneo por duas equipas cirúrgicas distintas, variante técnica descrita por Pompeo et al em 2013. 10 Apesar do potencial mostrado pela LIMVA, outras técnicas minimamente invasivas têm surgido, nomeadamente a LIMVA robótica 24 e a abordagem por via abdominal/hipogástrica, 25 com resultados comparáveis à LIMVA.…”
Section: Discussionunclassified
“…[6][7][8][9] A linfadenectomia inguinal por via aberta, procedimento clássico, associa-se a uma elevada taxa de complicações (>50%), nomeadamente infeção da ferida operatória, necrose da pele, edema dos membros inferiores e linfocelo. 7,[9][10][11][12] Em casos de doentes cN0, a linfadenectomia modificada é uma opção mais segura, consistindo na remoção de gânglios superficiais e da zona central, com preservação da veia safena magna. 9,13 Com o objetivo de diminuir cada vez mais a morbilidade do procedimento, foi desenvolvida a linfadenectomia inguinal modificada vídeo-assistida (LIMVA), respeitando os mesmos princípios oncológicos que a técnica clássica aberta.…”
Section: Introductionunclassified
“…In 2013 the feasibility was reported of simultaneously carrying out the EIL with a reduction in operation time and the benefits already described as for the minimally invasive technique [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%